Auditory Brainstem Response (ABR) simulator to enhance students understanding towards analyzing ABR waveforms - Dzulkarnain, Ahmad Aidil Arafat; Sapian, Faizah; Wilson, Wayne; Bradley, Andrew; Jamaluddin, Saiful Adli; Rahmat, Sarah; Norddin, Narina (2011)
BACKGROUND: The auditory brainstem response (ABR) can be defined as a complex response that represents neural activity generated at several anatomical sites in response to particular types of external stimuli (Hood 1998). The ABR typically consists of up to seven waves; each numbered using the Roman numeric system to give Waves I–VII (Jewett & Williston 1971). The ABR is widely used in neurological testing to determine the presence or absence of a disorder and to determine the site of the lesion for retrocochlear pathologies such as VIII never tumors.